Restorying Indigenous–Settler Relations in Canada: Taking a Decolonial Turn Toward a Settler Theology of Liberation - Morgan, Joëlle M. (Université Saint-Paul / Saint Paul University, 2018)
This dissertation explores some theological implications of restorying relations between settler and Indigenous peoples in Canada. In response to the call of the Seven Fires Prophecy, this work proposes that it is imperative that settler people seek and cultivate a new way to be in relationship with Indigenous peoples. Part of the aim of restorying is to overcome the social, cultural, political, and ecclesial erasure of Indigenous peoples. I construct a hybrid concept of settler coloniality to explore the logics of elimination and assimilation. I apply this methodological lens to key moments in modern Canadian hi/story, and the development of the All Native Circle Conference in The United Church of Canada. Employing autoethnographic tools, my research develops a transdisciplinary theological approach that is liberationist and seeks healing of wounded relations in Canada. The theological decolonial turn emerges out of the experience of a United Church community’s efforts toward right relations with Indigenous peoples on unceded Algonquin land. I weave together this community’s experience with key themes of Indigenous theologies and peace-building theory to construct a settler approach to decolonial healing. This liberationist theological approach points to an embodied metanoia, or transformation, of settler peoples. Such transformation can be experienced in relational spaces that risk both sides of story-telling: speaking or voice-ing and listening or hearing. The resurgence of oral traditions of Indigenous peoples create unsettling vibrations in the intimate aural spaces where settlers witness to and engage in a transformative decolonial healing praxis with Indigenous peoples.
Keywords: decolonial; settler; liberation theology; Canada; restory; Indigenous; relationship; coloniality; United Church of Canada; autoethnography; colonial wound; healing; aural; feminist